Noise assisted quantum key distribution (2019)
In this project, a quantum key distribution is implemented experimentally through the BB84 protocol. Likewise, a controllable quantum dephasing channel is used in the experimental setup to study the effects of decoherence in the implementation of the protocol. Finally, the possibility of reversing the effects of decoherence is studied through an inverse transformation that is explained both theoretically and experimentally.